Pengaruh Penggunaan Metode Questions Student Have Berbasis Critical Pedagogy dalam Pembelajaran Sejarah Terhadap Kemampuan Berpikir Historis Siswa - Edwin Mirzachaerulsyah; Devi .; Maria Ulfah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine how much influence the use of the student have question method based on Critical pedagogy has on students' historical thinking skills in history class X IPS 2 Madrasah Aliyah Mathla'ul Anwar Pontianak. In this study, experimental design was used with a quasi-experimental design pretest - posttest control group design. The population in the study were 52 students. The data collection tools used in this study were in the form of notes, interview guides, and historical thinking ability test questions, namely the pre-test and post-test. Based on the results obtained from before being given treatment the average value of students was 68.03 with the value of each student still being very low and below the KKM. Whereas after using the student behavior questions method based on critical pedagogy there was an increase from the average value of 68.03 to 75.19. By using the Cohen effect size calculation, the result is a value of 2.0713 in the high category. Therefore, by using the question student have method based on critical pedagogy in history learning, it can be seen that there is influence and increases the ability to think historically of class X IPS 2 Madrasah Aliyah Mathla'ul Anwar Pontianak